FACTORS AFFECTING FARMERS' RESPONSES TO THE USE OF COMBINE HARVESTERS IN VILLAGE MATANG PUNTONG, SEUNUDDON DISTRICT - Ulvia Fadilah; Suryadi Suryadi; Irada Sinta (Jurnal Mahasiswa Agribisnis, 2023)
This research was conducted in Village Matang Puntong, Seunuddon District, North Aceh Regency. This study aims to determine wheter the factors of land area, level of education, labor skills and loss of yields can affect farmers responses to the use of rice harvesting machines (Combine harvester) in Gampong Matang Puntong, Seunuddon District. The research methoud used is a survey method with a questionnaire as a tool. Sampling using simple random sampling with a total sample of 50 respondents. Data analysis using Likert scale and Multiple Linear Regression using SPSS software. the results of this study indicate that simultaneously (F test) shows that the factorsofland area, education level, Experience, labor expertise and crop loss have a significant effect on farmers responses. The results of partial test analysis (t test) showed that the factors of land area, experience and yield loss had a significant effect on farmers responses, while the level of education and labor expertise had no significant effect on farmers responses to the use of rice harvesting (Combine harvester) in Village Matang Puntong, Seunuddon District.